Effect of Season and Dietary Protein Level on Some Haematological Parameters and Blood Biochemical Compositions of Three Broiler Strains - Mohamed, E.A.A.; Ali, O.H.A.; Malik , Huwaida, E.E.; Yousif, I.A. (International Journal of Poultry Science, 2012)
The objectives of the present study were to investigate the effect of season (summer versus winter) and dietary protein level (high versus low) using three broiler strains (Ross, Cobb and Hubbard) on some physiological parameters; haematological parameters, haematological indices, serum metabolites and serum inorganic elements. Three hundred and sixty, one-day-old unsexed broiler chicks, were used during the summer and winter seasons, 120 from each strain. The number of chicks of each strain was divided into two groups, with six replicates (10 chicks per each). Group A of each strain was fed on a starter diet containing 23% crude protein for the first four weeks of age, replaced by a finisher diet containing 21% crude protein. Group B was fed on a starter diet containing 21% crude protein replaced by a finisher diet containing 19% crude protein. In both Cobb and Hubbard strains, the Packed Cell Volume (PCV) decreased significantly (P